7. ADL/IADL limitations and related factors in older adults in 3 Northern provinces Vietnam - Tuyet, Phuong Anh; Huyen, Nguyen Thi Thu; Long, Pham Ngoc; Bich, Pham Thi Ngoc; Toan, Tran Khanh (Tạp chí Nghiên cứu Y học, 2023)
This cross-sectional study aimed to identify the prevalence and factors related to the activities of daily living (ADLs) and instrumental activities of daily living (IADLs) among elderly people in Ha Noi, Ninh Binh, and Quang Binh in 2018. In total, 2448 participants were interviewed and measured using an adapted short version of Katz ADL Index and Lawton IADL Scale. The study showed a high prevalence of ADL and IADL disability (29.1% and 33.1%, respectively) in older adults. The risks of ADL and IADL limitations increased with age, gender ( higher in females), individuals withlower incomes, who had a history of chronic diseases, who self-rated poor health status, reported a moderate or severe somatic pain and who had weak grip strength. People who were still employed and regularly performed heavy physical activities had a lower chance of ADL and/or IADL limitations. We suggest that ADL/IADL limitations should be taken in account for any potential health care strategies and interventions for elderly population.